THE INFLUENCE OF PRINCIPAL LEADERSHIP, WORK MOTIVATION, AND WORK DISCIPLINE ON THE PERFORMANCE OF VOCATIONAL SCHOOL TEACHERS IN CLUSTER 3 OF SOUTH TANGERANG CITY - Kamsidik Kamsidik (International Journal Multidisciplinary Science, 2024)
This research aims to examine and analyze the influence of school principal leadership, motivation and work discipline on the performance of vocational school teachers in cluster 3 of South Tangerang City. Data collection was carried out through distributing questionnaires and carried out on 154 teachers. Data analysis in this research used SPSS version 21. The sampling technique used was the census method and the data testing techniques used in this research included validity testing with factor analysis, reliability testing with Cronbach's Alpha. Test classical assumptions and multiple linear regression analysis, to test and prove research hypotheses. The results of the analysis show that the principal's leadership has a positive effect on employee performance. Motivation has a positive effect on teacher performance and work discipline has a positive effect on teacher performance.